KOMPETENSI GURU SKI DI SD IT HIDAYATUL JANNAH KABUPATEN DELI SERDANG - Abdul Gani Jamora Nasution; Fadiah Adlina; Adelina Br Sembiring; Dinda Patliana Sukma (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2022)
The development of student learning creativity is inseparable from the role of teacher competence as an educator in transferring effective learning, as well as in SKI learning. This paper aims to see how the four SKI teacher competencies are implemented at SD IT Hidayatul Jannah. This study used a qualitative approach with an analytical descriptive method. As for the results of the study: (1) There are aspects of pedagogic competence that have been fulfilled, it can be seen that the teacher has provided educational learning, can communicate and interact actively, (2) Aspects of personality competence as seen by the stability and personal integrity of a teacher, being fair, honest, objective, and also disciplined in carrying out assignments, (3) Aspects of professional competence that can be seen from the mastery of material, structure, and also scientific thinking concepts that support the subjects that the teacher already has, (4) Aspects of social competence of teachers who can accept the advantages and disadvantages of others, and are able to adapt to the environment, especially to students.